Classification of parts used in mechatronic products and produced by permanent-mold casting methods. Issue 1 (June 2020) - Zaharinov, V; Malakov, I; Nikolov, S; Dimitrova, R; Stambolov, G
Abstract: The paper presents the results from a research on parts used in mechatronic products and produced by the permanent-mold casting methods of gravity die casting and die casting. An overview and analysis of different definitions for mechatronic systems and examples of mechatronic products is made. As a result, a new definition for a mechatronic product is proposed. Various classifications of mechatronic products are analysed and deemed too general for the purposes of the current research. Permanent-mold casting methods are analysed and their advantages and disadvantages are pointed out. Arguments as to why these methods are suitable for producing mechatronic product parts are given. Based on the proposed definition for mechatronic product, the analysed classifications, and the overview of the permanent-mold casting methods a new classification is proposed. The classification is used for classifying permanent-mold cast parts used in mechatronic products. The parts are classified in six groups with regard to their application in the mechatronic product. In addition, the classification gives information regarding permanent-mold casting method used, material, and mechatronic product that includes the part.